PENGARUH PROFITABILITAS, LEVERAGE, DAN LIKUIDITAS TERHADAP RETURN SAHAM DENGAN NILAI TUKAR SEBAGAI VARIABEL MODERASI PADA SAHAM LQ-45 - Anis Sutriani (STIE Perbanas Surabaya, 2014)
The investors purpose is to get the stock return so that they should pay attention to the rise and fall of financial performance, macro factors that can affect stock return. This study examines (1) simultaneously the effect of profitability, leverage, and liquidity on stock return (2) partially the positive effect of profitability and leverage on stock return (3) partially the effect of liquidity on stock return (4) the exchange rate as a variable moderating the effect of profitability, leverage, and liquidity on stock return. Stock return is dependent variable, while profitability, leverage, and liquidity are the independent variables. The samples consists of listed companies in LQ-45, period 2008-2011 which were taken by purposive sampling from the 79 companies listed in Indonesia Stock Exchange but only 14 companies as sample. Multiple regression and multiple regression analysis with interaction were used for analysis test. The result shows simultaneously return on assets, debt to equity ratio, cash ratio have no effect on stock return and partially only return on asset (?=5%) and debt to equity ratio (? =10%) have effect on stock return. When exchange rate is used as a moderating variable, it was found that return on asset and debt to equity ratio was not moderating variable on stock return.